The Singapore brand - Ju, Xinhang (2011)
Singapore is a resource-strapped island city that lives and dies by its global position. Relying on its position as a pro-business and efficient city, Singapore attracted talents, investments and companies to drive its economy. Now, as Singapore moves towards the new era, it realises that it is has entered a different ball game. The fight now is for global creative talent who are believed to be able to give the economy an edge over others. Yet, Singapore's older, more dominant image comes at odds with the aspired creative city image that tend to be a magnet for creative people. Thus, tension arises when a whole nation tries to change its very being for the purposes of branding.